Mesobuthus Venom-Derived Antimicrobial Peptides Possess Intrinsic Multifunctionality and Differential Potential as Drugs - Gao, Bin; Zhu, Shunyi (Frontiers in Microbiology, 2018)
Animal venoms are a mixture of peptides and proteins that serve two basic biological functions: predation and defense against both predators and microbes. Antimicrobial peptides (AMPs) are a common component extensively present in various scorpion venoms (herein abbreviated as svAMPs). However, their roles in predation and defense against predators and potential as drugs are poorly understood. Here, we report five new venom peptides with antimicrobial activity from two Mesobuthus scorpion species. These α-helical linear peptides displayed highly bactericidal activity towards all the Gram-positive bacteria used here but differential activity against Gram-negative bacteria and fungi. In addition to the antibiotic activity, these AMPs displayed lethality to houseflies and hemotoxin-like toxicity on mice by causing hemolysis, tissue damage and inducing inflammatory pain. Unlike AMPs from other origins, these venom-derived AMPs seem to be unsuitable as anti-infective drugs due to their high hemolysis and low serum stability. However, MeuTXKβ1, a known two-domain Mesobuthus AMP, is an exception since it exhibits high activity towards antibiotic resistant Staphylococci clinical isolates with low hemolysis and high serum stability. The findings that the classical AMPs play predatory and defensive roles indicate that the multifunctionality of scorpion venom components is an intrinsic feature likely evolved by natural selection from microbes, prey and predators of scorpions. This definitely provides an excellent system in which one can study how a protein adaptively evolves novel functions in a new environment. Meantimes, new strategies are needed to remove the toxicity of svAMPs on eukaryotic cells when they are used as leads for anti-infective drugs.